Analyzing intra-cycle velocity profile during wheelchair racing propulsion: a preliminary study - Poulet, Y.; Loisel, J.; Sauret, C. (ISBS Proceedings Archive (Michigan), 2022)
Recent technological improvements made it possible to monitor manual wheelchair (MWC) racing intra-cycle velocity profile under in-situ conditions. Based on the hypothesis that the intra-cycle velocity profile is related to the contribution of the upper body in racing MWC propulsion, it could be used for in-situ technical analysis. Four elite MWC racing athletes were equipped with IMUs during a 400 m race, and propulsion cycles were studied once constant speed was reached. Trunk flexion angle and trunk flexion speed were monitored, as well as manual wheelchair linear velocity. This preliminary study shows that intra-cycle velocity profile appears to be athlete specific. Future research coupling such measurements with pushrim contact detection systems could help further understanding the complexity of MWC racing propulsion`s technique and timing.